Adaptive image enhancement - Khalifa, Othman Omran; Abd Wahid, Amir Faliq (2016)

(untitled)
Currently we are living in digital era. Therefore, the image multimedia is a crucial issue in our daily life. It may be categorized the digital multimedia over still image or a video image. Digital multimedia transmission helps everyone to keep information fresh where they can access it everywhere, anytime. In this paper, an adaptive image enhancement using different enhancement technique was developed. The focus in this work is to create an adaptive program that can improve the appearance of digital images by clicking on a single button. Images might suffer from the lack of brightness, overexposed to luminance, blurriness and noise from low light exposure. The adaptive image enhancement used different types of enhancement techniques in spatial domain. The results from the simulation shows the value of peak signal to noise ratio and the mean square error that will be used to calculate the difference in both original and enhanced images.